The Unresolved Pathophysiology of Lymphedema - Azhar, Syaza Hazwany; Lim, Hwee Ying; Tan, Bien-Keem; Angeli, Veronique (Frontiers in Physiology, 2020)
Lymphedema is the clinical manifestation of impaired lymphatic transport. It remains an under-recognized and under-documented clinical condition that still lacks a cure. Despite the substantial advances in the understanding of lymphatic vessel biology and function in the past two decades, there are still unsolved questions regarding the pathophysiology of lymphedema, especially in humans. As a consequence of impaired lymphatic drainage, proteins and lipids accumulate in the interstitial space causing the regional tissue to undergo extensive and progressive architectural changes including adipose tissue deposition and fibrosis. These changes are also associated with inflammation. However, the temporal sequence of these events, the relationship between these events and their interplay during the progression are not clearly understood. Here, we review our current knowledge on the pathophysiology of lymphedema derived from human and animal studies. We also discuss the possible cellular and molecular mechanisms involved in adipose tissue and collagen accumulation during lymphedema. We suggest that more studies should be dedicated to enhance our understanding of the human pathophysiology of lymphedema to pave the way for new diagnostic and therapeutic avenues to this condition.